Effectiveness of public health education programs in improving healthy living behaviors: a systematic review - Nofita Tudang Rombeallo; Nasri Nasri; Evi Damayanti (Edukasi Ilmiah Indonesia, 2025)
Introduction: Public health education plays an important role in promoting healthy living behaviors and reducing the burden of preventable diseases. However, the effectiveness of various health education programs in consistently changing individual behavior is still a topic of scientific discussion. This study aims to assess the effectiveness of public health education programs in improving healthy living behaviors, such as increased physical activity, healthy diet, smoking cessation, and adherence to preventive health checks. Research Methodology: This systematic review follows the PRISMA guidelines and includes a literature search from PubMed, Scopus, and Web of Science databases for studies published between 2010 and 2024. Included studies should evaluate public health education interventions aimed at improving one or more healthy living behaviors in the general population. Data were collected and analyzed qualitatively and quantitatively to assess the impact of the intervention. Results: Of the 3,267 articles identified, 42 studies met the inclusion criteria. The majority of effective programs combine a community-based approach, digital media, and local stakeholder engagement. Overall, there was a significant improvement in healthy living behaviors in the intervention group compared to the control group, with the most pronounced effect on increased fruit and vegetable consumption and increased frequency of physical activity. Conclusion: Public health education programs are generally effective in promoting healthy living behaviors, especially when designed in a participatory manner and based on local contexts. These results support the importance of health policy development that encourages educational interventions as part of a sustainable health promotion strategy